Pemanfaatan Akun Instagram Ruang Nderes Dalam Meningkatkan Resiliensi Psikologis Penghafal Al-Quran - Muhammad Anas Kamaluddin; Abdullah Muhammad Al Kaff; Khusni Nur Rohman; Zainal Arifin Ahmad (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to explore the potential of the Ruang Nderes Instagram account in improving the psychological resilience of Quran memorizers. Using a qualitative method with a case study approach, data was collected through interviews with the account manager and two active followers to understand their experiences and perceptions regarding the content. The results show that the psychological resilience of Quran memorizers is influenced by internal factors such as spiritual commitment, self-efficacy, and emotional regulation, as well as external factors such as digital social support. Ruang Nderes content, such as inspirational stories, motivational reels, and humortivation, strengthens psychological resilience by creating a sense of community and indirect learning from collective experiences. Users view the content as a holistic support that transforms memorization challenges into growth opportunities, while the manager emphasizes content strategies to maintain intention and istiqomah. This study concludes that Ruang Nderes serves as a digital mentorship model that integrates Quranic values with technology, supporting resilient huffaz in the digital era.